Submandibular gland cancer: Specific features and treatment considerations. Issue 1 (30th October 2017) - Aro, Katri; Tarkkanen, Jussi; Saat, Riste; Saarilahti, Kauko; Mäkitie, Antti; Atula, Timo
Abstract: Background: In the absence of unified treatment protocol, we evaluated the management and outcomes of submandibular gland cancers in an unselected patient series. Methods: We included all patients with resected submandibular gland cancer treated at the Helsinki University Hospital from 2000 to 2010 with a 5‐year minimum follow‐up. Results: Twenty‐five patients with cancer represented 30% of submandibular gland neoplasms, and most were adenoid cystic carcinomas (ACCs; 56%). At presentation, 3 patients showed clinical signs of probable malignancy. Of 22 neck dissection specimens, 5 patients (20%) had metastases with an occult metastasis rate of 4%. Cancer recurred in 11 patients (44%), of which 7 (28%) were only at a distant site. The 5‐year disease‐specific survival (DSS) and overall survival (OS) rates were 76%, and disease‐free survival (DFS) was 68%. Conclusion: Most tumors were ACCs differing from the histological pattern of parotid gland cancers. Occult metastases were rare. The rarity of submandibular gland cancer, its variable histological pattern, and varying biological behavior warrant centralized management.